SURVEI KONDISI FISIK ATLET TINJU AMATIR PUTRI KABUPATEN NGAWI DALAM RANGKA PERSIAPAN PORPROV JAWA TIMUR TAHUN 2023 - Veronika Rini Alsukma; Kartika Setianingrum; Aba Sandi Prayoga (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2023)
Boxing is a sport and martial art in which two participants of similar weight compete against each other using their fists in a series of one- or three-minute intervals called rounds. The purpose of this study was to determine the physical condition of female amateur boxing athletes in Ngawi Regency in preparation for the 2023 East Java Province Sports Week. This type of research is a quantitative descriptive study using a survey method. The samples used in this study were all female amateur boxing athletes from Sasana Soerjo Ngawi, totaling 10 athletes. Data collection techniques in this study used tests and measurements. The results of this study indicate that the average female amateur boxing athletes at Sasana Soerjo Ngawi are in good condition, meaning that overall athletes are ready to take part in the East Java Province Sports Week. Even so, there are still some aspects that are in moderate condition, such as endurance and abdominal muscle strength. To ensure optimal readiness in Porprov, women's boxing athletes in Ngawi District need to maintain health and consistency in training, manage a balanced diet, and provide sufficient recovery time for their bodies. It must reflect the entire substance of the article and be able to help readers determine its relevance. with interest and decide whether to read the document in its entirety.